1998
DOI: 10.1139/x97-218
|View full text |Cite
|
Sign up to set email alerts
|

Responses of hardwood advance regeneration to seasonal prescribed fires in oak-dominated shelterwood stands

Abstract: Effects of seasonal prescribed fires of varying intensities on density, mortality, stem form, height, and height growth of hardwood advance regeneration were investigated. Three mixed-hardwood stands on productive upland sites were cut using a shelterwood technique, each forming a block of spring burn, summer burn, winter burn, and control treatments. Advance regeneration was inventoried from permanent plots before and after burning. Fires top-killed nearly all hardwood regeneration, forcing the rootstocks to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(94 citation statements)
references
References 23 publications
5
87
2
Order By: Relevance
“…The numbers of yellow-poplar seedlings decreased by the third measurement at both sites and even more after the second burn in North Carolina. This result agrees with the results of Brose and Van Lear (1998) who emphasized the need for prescribed burning after yellow-poplar seedlings become established. Oaks were 4 to 6 times more numerous after the second burn in North Carolina than were seedlings of yellow-poplar.…”
Section: Dual Firessupporting
confidence: 92%
“…The numbers of yellow-poplar seedlings decreased by the third measurement at both sites and even more after the second burn in North Carolina. This result agrees with the results of Brose and Van Lear (1998) who emphasized the need for prescribed burning after yellow-poplar seedlings become established. Oaks were 4 to 6 times more numerous after the second burn in North Carolina than were seedlings of yellow-poplar.…”
Section: Dual Firessupporting
confidence: 92%
“…It is essential that the fire manager knows that the software is an auxiliary tool and the decisions must not be taken based solely on its simulations. Some authors consider that the "Behave" system has more efficient results especially when the values of the characteristics of the fuel are measured and used directly (methodology adopted in this work), instead of using some standard fuel model (GRABNER et al, 1997;BROSE, 1997). However some errors may still occur when the diversity of the fuel is not considered, assuming that conditions are constant.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of their high root:shoot ratio and often the lower position (more protected) of dormant buds, oaks and hickories are considered to be better able to continue to sprout after repeated top-kills and also more resistant to dormant bud damage during high intensity fires (Van Lear and Watt, 1993;Brose and Van Lear, 1998). A single low-intensity fire, however, provides favorable conditions for rapid growth for light-seeded species (e.g., red maple), seed-banking species Table 1 and text for details on the classes.…”
Section: Effects Of Thinning and Burningmentioning
confidence: 99%
“…Kruger and Reich (1997a,b) found that a single prescribed fire applied to small openings in young, mesic oak stands in Wisconsin favored red oak regeneration over competitors. Brose and Van Lear (1998) showed that a combination of shelterwood harvest with a single fire (particularly effective were spring growing-season fires) favored oak regeneration over red maple and yellow-poplar in the Virginia Piedmont. Each of these studies varies in forest age and structure, land-use history, site quality, treatments, and results; however, all provide insights to build on in order to address some of the difficulties associated with oak regeneration.…”
Section: Effects Of Thinning and Burningmentioning
confidence: 99%